Fabrikasi Hunian Sementara untuk Pasca Bencana - Dyah Puspa Ayu; Budi Prayitno; Agus Haryadi (Unika Soegijapranata Semarang, 2020)
Indonesia is an inseparable state of the earthquake. As a result of the earthquake, many victims lost their homes. The victims had to stay in isolation for a long time. From that, the victim needs assistance in the form of shelter, but the housing can’t be built easily. Then a temporary building is needed a transition phase to house assistance is still being developed. The government is currently unable to provide maximum temporary shelter. The purpose of this study is to find the right model for temporary shelter assistance in post-disaster situations used in refugee locations in Indonesia and abroad. The research method uses a literature review by comparing the temporary shelter model and the study model as a comparison of occupancy dimensions. Temporary shelter is the residence required during post-disaster and can be produced in fabrication. Fabrication for temporary housing is related to connection, material, packaging, demolition, and distribution system. It aims to maximize on-site assistance, facilitating the installation and distribution of temporary shelter.